Are We Ready for Cell Therapy to Treat Stroke? - Rascón-Ramírez, Fernando José; Esteban-García, Noelia; Barcia, Juan Antonio; Trondin, Albert; Nombela, Cristina; Sánchez-Sánchez-Rojas, Leyre (Frontiers in Cell and Developmental Biology, 2021)
Clinical trials of cell therapies that target stroke began at the beginning of this century and they have experienced a significant boost in recent years as a result of promising data from basic research studies. The increase in the information available has paved the way to carry out more innovative and varied human studies. Efforts have focused on the search for a safe and effective treatment to drive neuro-regeneration in the brain and to reduce the sequelae of stroke in patients. Therefore, the aim of this review is to evaluate the clinical trials using cell therapy to treat stroke published to date and assess their limitations. From 2000 to date, most of the published clinical trials have focused on phases I or II, and the vast majority of them demonstrate that stem cells are essentially safe to use when administered by different routes, with transient and mild adverse events that do not generally have severe consequences for health. In general, there is considerable variation in the trials in terms of statistical design, sample size, the cells used, the routes of administration, and the functional assessments (both at baseline and follow-up), which makes comparing the studies complicated. From this overview, it is apparent that the experimental protocol is the main element that can be improved in future studies. Establishing an adequate experimental and statistical design will be essential to obtain favourable and reliable results when conducting phase III clinical trials. Thus, it is necessary to standardize the criteria used in these clinical trials in order to aid comparison. In the near future, cell therapy will be a key approach in the treatment of stroke if adequate and comprehensive levels of recovery are to be achieved.